Internalisasi Nilai-Nilai Pendidikan Karakter melalui Kegiatan Ekstrakurikuler Pencak Silat di Sekolah Dasar - Nafi’a, Muhammad Zidni Ilman (Faculty of Teacher Training and Education of Undaris, 2025)
Character education in elementary schools is an important aspect in shaping a generation that is not only intellectually intelligent, but also has moral and social integrity. Pencak Silat extracurricular activities as non-formal activities are considered to have the potential to instill character values through physical training, discipline, and social interaction. However, previous studies have primarily focused on character education within formal curriculum and religious activities, leaving the use of Pencak Silat as a medium for character development in elementary schools largely unexplored. This study aims to address this gap and uncover the character values reflected in Pencak Silat extracurricular activities. This study employsa descriptive qualitative approach with a field study conducted at Sukoanyar Junior High School in Kediri. Data was collected through observation, in-depth interviews, and documentation, and analyzed through data reduction, data presentation, and conclusion drawing. Source and technique triangulation was used to ensure data validity. The research findings indicate that pagar nusa activities reflect 11 out of 18 character values as defined by the Ministry of Education and Culture, including: discipline, responsibility, hard work, tolerance, religiosity, social concern, love for peace, and independence. These values develop through the process of habit formation, the example set by coaches, and social interaction during training. These findings confirm that character education can be implemented contextually through non-formal activities based on direct experience.Keywords: Character education; Extracurricular activities; Martial Arts